The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1200/op.20.00473
|View full text |Cite
|
Sign up to set email alerts
|

Distress Screening Through Patient-Reported Outcomes Measurement Information System (PROMIS) at an Academic Cancer Center and Network Site: Implementation of a Hybrid Model

Abstract: PURPOSE: Cancer care guidelines recommend regular distress screening of patients, with approximately one in three patients with cancer experiencing significant distress. However, the implementation of such programs is variable and inconsistent. We sought to assess the feasibility of implementing a hybrid electronic and paper screening tool for distress in all patients coming to a large academic cancer center and an associated integrated network site. METHODS: Patients at an academic cancer center (Stanford Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…If shown to be concurrently valid, PROMIS may adequately replace PROMs and reduce both patient and physician burden. Previous studies have found that PROMIS sufficiently captures information obtained through disease-specific PROMs 4,5,14–16 . PROMIS is unique in that it utilizes an iterative CAT system, based on item response theory that improves flexibility, sensitivity, and efficiency 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If shown to be concurrently valid, PROMIS may adequately replace PROMs and reduce both patient and physician burden. Previous studies have found that PROMIS sufficiently captures information obtained through disease-specific PROMs 4,5,14–16 . PROMIS is unique in that it utilizes an iterative CAT system, based on item response theory that improves flexibility, sensitivity, and efficiency 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Disease specific PROMs and the more generic PROMIS instrument are increasingly used in spine and oncological patients. [15][16][17] PROMIS provides insight into a patient's health across a variety of health conditions and may therefore capture information provided by various disease specific PROMs. 18,19 If shown to be concurrently valid, PROMIS may adequately replace PROMs and reduce both patient and physician burden.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-reported improvements in mental health (GMH) in this study were especially noteworthy. Mental health support is critical considering that up to 65% of individuals with cancer report high levels of distress and depressive or anxious symptoms [17,[58][59][60]. In some cases, high levels of distress are related to unplanned healthcare use [61] and decreased adherence to cancer treatments [62].…”
Section: Discussionmentioning
confidence: 99%
“…Further, PROMIS domains demonstrated greater reliability over a broader range of symptom severity or functional impairment compared with SF-12 or SF-36 (31,32). The precise, versatile PROMIS item banks (administered either as four-or eight-item short forms, or computer adaptive test) have also already been used as outcome measures studies (33,34) and in clinical practice for symptom monitoring (35)(36)(37). In addition, PROPr, and the overall mental and physical health summary scores (38), provide reliable measures of health utility and overall HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated PROPr using scores generated from seven domains that may be assessed by PROMIS short forms and computer adaptive tests. These seven domains, as well as the total number of items included in the respective item banks, are as follows: depression (28), fatigue (95), physical function (165), sleep disturbance (27), ability to participate in social roles and activities (35), pain interference (40), and cognitive function abilities (31). The PROMIS short-form profiles PROMIS-57, PROMIS-43, and PROMIS-29 assess each domain using eight, six, or four items, respectively.…”
Section: Health Utility Measuresmentioning
confidence: 99%